Integration of Forestry Crops with Agricultural Crops Through Agroforestry Business Patterns in Central Lombok District - Husni, Syarif; Wangiyana, Wayan (Jurnal Biologi Tropis, 2024)
Agroforestry can be successful if it can increase people's income while maintaining land productivity. Research objectives: 1). knowing the pattern of agroforestry farming in North Batukliang District, 2). analyzing income, business efficiency and rice-equivalent farmer income in various agroforestry farming patterns in North Batukliang District. a total of 43 people were determined by dividing members of the population into several subgroups called starta, then a sample was selected from each stratum using the Stratified Random Sampling method. The results of the research show: 1) There are two agroforestry farming patterns implemented by HKm farmers in North Batukliang District, Central Lombok Regency, namely Pattern I is dominated by MPTS (Multy Purpose Tree Species) crops and Pattern II is dominated by annual crops, 2) Farmer income in pattern I is dominated MPTS (Multy Purpose Tree Species) plants amounting to Rp. 9,133,036/ha/year and income of pattern II farmers dominated by annual crops of Rp. 6,995,800/ha/year, 3) Pattern I agroforestry farming efficiency level is 3.56 and Pattern II is 2.96, and 4) Income farmers measured in rice equivalent is 911.33 kg per year for Pattern I and Pattern II is 699.68 kg.